Activated Leukocyte Cell Adhesion Molecule Modulates Th2 Immune Response in Atopic Dermatitis - Oh, Mi Seon; Hong, Jung Yeon; Kim, Mi Na; Kwak, Eun Ji; Kim, Soo Yeon; Kim, Eun Gyul; Lee, Kyung Eun; Kim, Yun Seon; Jee, Hye Mi; Kim, Seo Hyeong; Sol, In Suk; Park, Chang Ook; et al. (Allergy, asthma & immunology research, 2019)
Activated leukocyte cell adhesion molecule (ALCAM), a member of the immunoglobulin superfamily, is highly expressed on dendritic cells. ALCAM and its receptor CD6 are co-stimulatory molecules in the immunological synapse; their interaction is required for T cell activation. While atopic dermatitis (AD) is recognized as a T helper 2 (Th2)-mediated allergic disease, the role of ALCAM in its pathogenesis is unclear. ALCAM levels were measured in the serum of AD patients and AD-induced murine model by ovalbumin treatment. We next investigated transepidermal water loss, clinical score, Th2-immune responses, skin barrier gene expression and T-cell activation using wild-type (WT) and ALCAM deficiency mice. An oxazolone-induced AD-like model was also established and analyzed using WT- and ALCAM-deficient mice. We found that serum ALCAM levels were elevated in pediatric AD patients as well as WT AD mice, whereas Th2-type cytokine production and AD symptoms were suppressed in ALCAM-deficient mice. In addition, CD4⁺ effector T-cell counts in murine skin and skin-draining lymph nodes were lower in ALCAM-deficient mice than in their WT counterparts. ALCAM deficiency was also linked to higher expression of skin barrier genes and number of lamellar bodies. These findings indicate that ALCAM may contribute to AD pathogenesis by meditating a Th2-dominant immune response and disrupting the barrier function of the skin.